Analytical and experimental studies on ballistic impact behavior of carbon nanotube dispersed resin. (February 2015) - Pandya, Kedar S.; Naik, N.K.
Abstract: An analytical formulation is presented for the prediction of ballistic impact behavior of multi-walled carbon nanotube (MWCNT) dispersed epoxy resin. The formulation is based on stress wave propagation and energy balance between the projectile and the target. During the ballistic impact event, the energy lost by the projectile is absorbed by the target through various damage and energy absorbing mechanisms such as compression of the target directly below the projectile, compression in the region surrounding the impacted zone, shear plugging, formation of ring and radial cracks in the resin leading to tensile failure and energy absorbed due to the presence of carbon nanotubes. Complete failure of the target was due to catastrophic brittle fracture and shattering. Experimental studies are carried out on ballistic impact behavior of neat epoxy and MWCNT dispersed epoxy. Typical results on ballistic limit velocity and energy absorbed by various mechanisms are presented. Ballistic impact behavior of neat epoxy resin and MWCNT dispersed epoxy resin are compared. A good match is observed between the analytical and experimental results. Highlights: An analytical formulation is presented for ballistic impact behavior of MWCNT dispersed epoxy resin. Ballistic impact behavior of neat epoxy resin and MWCNT dispersed epoxy resin are compared. A good match is observed between the analytical and experimental results.